Psychosocial Development of the Gifted: Implications for a Counseling Intervention for Gifted Students - Sisk, Dorothy (Gifted education international, 2005)
Traditional approaches to the education of gifted children and youth have focused on cognitive dimensions, with a program emphasis of enriched and accelerated education, providing services in special classes, special schools, and in the regular classroom. In the current public school environment in the United States, considerable attention is being placed on raising standards and testing students. No piece of educational legislation in the past decade has stirred as much comment and controversy as the No Child Left Behind Act that includes a mandate for an extensive testing program across major subject areas (Gallagher, 2004). Academic success and cognitive development have become the focus of educational programs, especially for gifted students. Gifted students feel pressure to succeed; consequently, their emotional and social development is being neglected by the school (Fleith, 2001). This paper examines the critical importance of developing the emotional, social and personal self of the exceptional child who needs to understand the intensities and challenges of functioning fully as a gifted person. The paper includes a summary of the essential counseling interventions for Gifted students.